Tricuspid Valve Repair: Devega’s Tricuspid Annuloplasty in Moderate Secondary Tricuspid Regurgitation - Pradhan, S; Gautam, N C; Singh, Y M; Shakya, S; Timala, R B; Sharma, J; Koirala, B (Kathmandu University Medical Journal, 2012)
Background Moderate secondary tricuspid incompetence has variable natural history if left unattended during mitral valve surgery. Recent data suggest progression of the secondary tricuspid incompetence over time. Secondary moderate tricuspid regurgitation in rheumatic mitral valve disease may regress after mitral valve surgery without direct intervention. Objectives: The present retrospective comparative hospital based tudy was done to assess early result of DeVega tricuspid valve annuloplasty amongst those with moderate tricuspid regurgitation due to rheumatic mitral valve disease. Methods: Group I (mitral valve replacement with tricuspid repair) and Group II (mitral valve replacement only) were compared regarding functional class, heart rate, rhythm, cardiac dimensions, function and valve pathology. The two groups were followed up at three months post-operatively and evaluated for their functional class and echocardiography variables. The data was analyzed with SPSS 16.0 Results: There were 43 patients who underwent mitral valve replacement with moderate tricuspid regurgitation. Twenty three underwent mitral valve replacement with tricuspid repair group (Group 1). Most of the patients were women (28/43). The mean age was 31.4 + 14.8 and 25.13 + 9.4 years. Group I had 21(91.3%) and Group II had 17 (85%) in NYHA class III & IV. The pre-operative echocardiographic cardiac left ventricular and left atrial dimensions, left ventricular function and valve lesions were statistically similar for both groups, except PASP was higher amongst tricuspid repair (Group 1: 38.60 + 12.75mHg, Group 2: 61.52 + 19.76mmHg; p= <0.05). At three month’s review after surgery, four patients were in NYHA II amongst those without tricuspid repair (Group II), whilst the rest were in NYHA I. Left ventricular dimensions, Left Ventricular function and valve prosthetic valve function were similar between groups. Eleven (47.8%) patients in Group I and only five (25%) of Group II had trace or less TR at the follow-up (p < 0.05). There were 7 (16.2%) patients who had persistent moderate TR. Higher PASP and larger LV dimensions at three months were predictive of persistent moderate TR. Conclusion Mitral valve replacement does decrease the severity of tricuspid regurgitation amongst those with secondary moderate tricuspid regurgitation by at least one grade, but DeVega’s annuloplasty confers a better repair result. http://dx.doi.org/10.3126/kumj.v9i1.6266 Kathmandu Univ Med J 2011;9(1):64-8